(untitled) (Sociologisk Forskning, 2017)
Paradoxes of citizen formation: Citizenship positioning in stories about belonging in an era of migration This article analyzes the formation of citizenship in today’s multi-ethnic Sweden with a particular focus on how migration renders visible existing citizenship ideals, defined in terms of similarity and difference on the basis of ethno-cultural background. Analysing three individual stories of women who have migrated to Sweden, with different biographies and stories of how they ended up in Sweden, the article focuses on negotiations of the boundaries and contents of citizenship in multi-ethnic Sweden. The point of departure for the analysis is a post-structuralist and discursive approach. In all, the stories address the crucial question of who should be included into the social community and on what conditions – and who should be left out? This particular question is also at the very centre of the political debate in today’s Europe. On the one hand, there are strong arguments about the ’death of multiculturalism’ and demands for new forms of ethno-culturally graduated citizenship – also in Sweden. On the other hand, in Sweden as well as in other European countries, claims for the development of a new and more inclusive societal community have been raised, expanding the rights of citizens to accommodating also those who have been excluded from them.